2001
DOI: 10.3354/meps218275
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of northern bluefin tuna from nursery areas in the Pacific Ocean using otolith chemistry

Abstract: Otolith chemistry of juvenile Pacific bluefin tuna Thunnus orientalis was measured to assess differences in composition among 3 nursery areas in the North Pacific Ocean: East China Sea, Sea of Japan and the Pacific Ocean off Shikoku. Six elements (Li, Mg, Ca, Mn, Sr and Ba) were measured in whole otoliths using solution-based inductively coupled plasma mass spectrometry. Univariate contrasts of T. orientalis otoliths collected in 1994 and 1995 indicated that concentrations of 5 elements (Li, Mg, Ca, Mn, Sr) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 26 publications
4
75
2
Order By: Relevance
“…Samples were then left to dry overnight in a laminar flow cabinet. Since it has been previously shown that there is little difference in elemental chemistry between left and right sagittal otoliths of the same fish (Rooker et al 2001), only one randomly chosen otolith from each pair was used. Each otolith was then weighed using a Mettler Toledo microbalance to the nearest 0.001 g. Otoliths were encased in Araldite ep oxy resin blocks (Agar Scientific), and a 200 µm transverse section was then taken either side of the core using a Buehler precision low-speed sectioning saw.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were then left to dry overnight in a laminar flow cabinet. Since it has been previously shown that there is little difference in elemental chemistry between left and right sagittal otoliths of the same fish (Rooker et al 2001), only one randomly chosen otolith from each pair was used. Each otolith was then weighed using a Mettler Toledo microbalance to the nearest 0.001 g. Otoliths were encased in Araldite ep oxy resin blocks (Agar Scientific), and a 200 µm transverse section was then taken either side of the core using a Buehler precision low-speed sectioning saw.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies using chemical signatures in otoliths have shown that these natural markers are valuable for evaluating the origin and movement of tunas in the Pacific Ocean (Rooker et al 2001, Wang et al 2009, Shiao et al 2010. The principal assumption underlying this approach is that the otolith accretes material as the fish grows and the chemical composition of the otolith is related to the physicochemical conditions of the water mass inhabited (Rooker et al 2001).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…The principal assumption underlying this approach is that the otolith accretes material as the fish grows and the chemical composition of the otolith is related to the physicochemical conditions of the water mass inhabited (Rooker et al 2001). Therefore, material deposited in the otolith during the first weeks to months of life may serve as a natural tag of an individual's place of origin.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 1 more Smart Citation
“…This decline could not only compromise the fisheries continuity, but also affect the productive socioeconomic sector that depends on them (Beck et al, 2001). Due to the strong relation between chemistry and morphometry of fish otolith with different environmental features, lately these tools have been widely used to identify breeding areas of different commercially important species (Rooker et al, 2001;Gillanders et al, 2003;Tournois et al, 2013;2015d;Bailey et al, 2015;Bouchard et al, 2015). Even though physiological factors can affect incorporation of trace elements in the otolith, temperature and salinity are among the most relevant environmental factors regarding the incorporation of elements in this structure (Campana, 1999;Secor & Rooker, 2000;Elsdon & Gillanders, 2002;Martin et al, 2004;Sturrock et al, 2012;Bouchard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%